2018
DOI: 10.1007/s00417-018-4138-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinal pigment epithelium hyperplasia overlying pigment epithelial detachment in age-related macular degeneration can masquerade as neovascularization on optical coherence tomography angiography

Abstract: PurposeTo report the image artifacts due to retinal pigment epithelium (RPE) hyperplasia overlying retinal pigment epithelial detachment (PED) in age-related macular degeneration (AMD), which can masquerade as neovascularization on optical coherence tomography angiography (OCTA).MethodsA hospital-based, retrospective, and cross-sectional study. Twenty-two eyes from 16 patients with non-vascularized PED related to AMD were included in this study. All patients were examined by OCTA, spectral-domain optical coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It was observed in the present study that the mean age of the patients in the study group was significantly higher than in the control group, as well as the means of the superficial FAZ areas of both eyes. Thus, it can not be affirmed that the increase in FAZ was observed due to arterial hypertension, since with increasing age there is a decrease in vascular density of the retina and an increase in FAZ in both the superficial and deep plexuses [24][25][26].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was observed in the present study that the mean age of the patients in the study group was significantly higher than in the control group, as well as the means of the superficial FAZ areas of both eyes. Thus, it can not be affirmed that the increase in FAZ was observed due to arterial hypertension, since with increasing age there is a decrease in vascular density of the retina and an increase in FAZ in both the superficial and deep plexuses [24][25][26].…”
Section: Discussionmentioning
confidence: 97%
“…However, such enlargement is not easily interpreted, since there is variation in the size of this area also in the general population, since in a single individual this measurement can usually be large or abnormally increased. Thus, given its individual variation, a personalized evaluation of the same and its relationships with the other layers of the retina is suggested [24].…”
Section: Discussionmentioning
confidence: 99%
“…We applied the RPE-fit segmentation strategy combined with manual adjust, given polypoidal lesions located between the Bruch membrane and RPE. This segmentation strategy also eliminated the masking artifacts due to hyperreflective material overlying or within the PED [49,50]. In addition, focal RPE atrophy that accompanied by PED gave rise to unmasking artifacts [49].…”
Section: Discussionmentioning
confidence: 99%
“…[32] Chen et al demonstrated that RPE hyperplasia overlying PED may cause false flow signal in deeper layers. [33] Projection artifact can be used to examine the anatomy of the choroidal vessels. By moving and placing the segmentation line behind the choroid, the vascular pattern of choroidal vessels can be projected onto the sclera.…”
Section: Misidentification Of Retinal Layers (Segmentation Artifact)mentioning
confidence: 99%